Development of an E-Module Based on Multiple Representation Integrated with Islamic Education to Improve Scientific Literacy and Learning Independence of Students on Buffer Solution Material - Afifah Khairanirani; Zamsiswaya Zamsiswaya; Irfan Mohd Fauzi (Journal of Natural Science and Integration, 2025)
This study aims to develop a multiple-representations-based e-module to enhance students’ scientific literacy and learning autonomy in the topic of buffer solutions. The research employed a Research and Development (R&D) methodology using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Expert validation and limited trials involving teachers and students from three senior high schools in Pekanbaru were conducted to assess the e-module. The results indicate that the e-module is valid, practical, and effective in improving both conceptual understanding and learners’ autonomy. Beyond enhancing academic performance, the integration of multiple representations enables students to interrelate macroscopic, submicroscopic, and symbolic levels of chemical concepts. Moreover, the e-module incorporates Islamic educational values, emphasizing the integration of scientific knowledge with spiritual and ethical dimensions to foster holistic learning. These findings suggest that representation-based digital learning tools can serve as an effective strategy for promoting scientific literacy and self-regulated learning in chemistry education.Keywords: e-module, multiple representation, scientific literacy, learning independence, buffer solutions, islamic education.